Legal protection against women from domestic violence in the Baubau City - La Gurusi; Edy Nurcahyo (Jurnal Hukum Volkgeist, 2019)
The fenomenon of domestic violence, especially against women, becomes a serious social problem. Law enforcement is required in order to eliminate domestic violence. The purpose of this study is to find out how the form of legal protection against women as victims of violence in households and to know what factors affect the occurrence of violence in the household. This research method using normative law research method. The data used is secondary data from the Baubau city resort police in 2017. Data were analysis using qualitative analysis. The results of the study indicate that the form of legal protection against women as victims of violence in households is the protection of preventive and repressive law. In two forms of legal protection, preventive law protection is more dominant than repressive.